On the implementation of the provisions regarding environmental impact assessments under the BBNJ agreement - Wang, Chuanliang; Li, Yuxin (Frontiers in Marine Science, 2025)
The Agreement under the United Nations Convention on the Law of the Sea on the conservation and sustainable use of marine biological diversity of areas beyond national jurisdiction (BBNJ Agreement) was adopted on June 19, 2023. Part IV of the BBNJ Agreement focuses on the environmental impact assessments (EIAs) in areas beyond national jurisdiction (ABNJ) from the following aspects: objectives and the general obligation of Parties to conduct EIAs, the relationship between BBNJ Agreement and EIA processes under relevant legal instruments and frameworks and relevant bodies, the EIA process, monitoring and review mechanisms, the function of the Scientific and Technical Body, and Strategic Environment Assessment. However, to facilitate the adoption of the Agreement, many compromises were made by the Parties. As a package agreement, the provisions regarding EIAs under the BBNJ Agreement are ambiguous and contain gaps. Moreover, during the implementation of the Agreement, different Parties have different interests and positions, which poses challenges for implementing the provisions. For example, environmental NGOs advocate for the strict application of the precautionary principle, which necessitates demonstrating the absence of significant environmental impact before the approval of potentially harmful activities. In contrast, major fishing nations prefer to rely on existing regional management frameworks to prevent redundant assessments and avoid additional economic burdens. In this regard, attention should be given to the overall interests and needs of the international community, and the effective implementation of the provisions regarding EIAs under the Agreement should be promoted through refining the regulations of the Agreement, establishing cooperative mechanisms, and creating frameworks for shared benefits.